ICT as a Contribution to Ecuadorian Emerging Tourism in Regional Contexts, Balsapamba, San Miguel, Bolívar Province - Oleas-Orozco, José (2023)
Tourism currently constitutes a financial income for developing countries. However, the tourism management depends of public and private administration. In Ecuador, geographical conditions, nature, biodiversity, culture, and more have great potential as tourist attractions. The state administration prioritizes natural places, heritage sites and cultural representations located in main cities. Therefore, new and emerging regional initiatives have difficulties in dissemination and communication. In this scenario, ICTs constitute an alternative and economic way to spread new and potential tourist destinations. This research analyzes the ICT usefulness, such as mobile devices applications or APP, within an emerging tourist destination such as the Balsapamba parish, of Bolívar province. The study was carried out in two stages, an exploratory stage with a mixed approach (qualitative and quantitative), to know the communication status and tourist attractions diffusion. Also, it was inquired about ICT tourists’ habits. The info allows to produce an APP with tourist content. The second stage consisted of APP testing and verifying its usefulness and contents relevance. The results showed an effectiveness greater than 90%, relevance of content greater than 85% and technological usability satisfaction tool equal to 100%. The great versatility of ICT in the tourism field can be inferred for new destinations dissemination, not been considered by public administrations.